The Association of Polycystic Ovary Syndrome-Like Clinical Features and Socioeconomic Status on Health-Related Quality of Life - Stephanie Mohammed; Venkatesan Sundaram; Brian N. Cockburn; Shastri Motilal; Sasha Ottey; Ricardo Azziz (Women's Health Reports)
Background: Polycystic Ovary Syndrome (PCOS) affects 8%–13% of reproductive-age women globally, with comorbidities including obesity, insulin resistance, type 2 diabetes, and psychological disorders. Socioeconomic status (SES) significantly impacts health outcomes. Methods: A community-based, pilot study was conducted in Trinidad among females aged 18–45 years, representing diverse ethnicities and SES. Participants underwent a standardized history and physical exam. Clinical hyperandrogenism (HIR) was assessed using the modified Ferriman–Gallwey scale (HIR ≥6), menstrual dysfunction (MD) as <9 cycles/year, depression via Beck’s Inventory, overall health using SF-12 v1, and daytime somnolence with the Epworth Sleepiness Scale. Data analysis included descriptive statistics, analysis of variance, and multinomial logistic regression adjusting for confounders. Results: Among 250 participants (mean age 31.6 ± 7.9 years), we classified 200 with clinical presentations, which included: no MD or HIR (56.7%), MD only (14.4%), HIR only (21.9%), and MD+HIR (7%). Age, income, and education were significantly correlated with clinical presentation. Older age reduced the risk of HIR (mean difference = 4.507, p = 0.004) and MD+HIR (mean difference = 9.063, p < 0.001). Income (OR = 0.37, 95% CI: 0.16–0.87, p = 0.022) reduced MD odds. Self-reported infertility was associated with MD (odds ratio [OR] = 0.27, 95% confidence interval [CI]: 0.11–0.65, p = 0.006). MD+HIR correlated with severe depression (OR = 5.96, 95% CI: 1.62–21.90, p = 0.007). Mental health scores (SF-12 MCS) were lower in women with MD+HIR (mean difference = −11.477, p = 0.005). Conclusion: Seven percent of women in this sample showed probable PCOS based on clinical manifestations, with SES impacting quality of life, mental health, and sleep. Higher income reduced MD and MD+HIR risk, while infertility increased MD risk and severe depression was linked to MD+HIR.